Case Report: Amyloidosis Cutis Dyschromica: Dermoscopy and Reflectance Confocal Microscopy and Gene Mutation Analysis of a Chinese Pedigree - Wang, Hui; Zhong, Zhenyu; Wang, Xiuli; Zheng, Liyun; Wang, Yifan; Wang, Shan; Liu, Siqi; Li, Hui; Guo, Ze; Gao, Min (Frontiers in Medicine, 2021)
Background: Amyloidosis cutis dyschromica (ACD) is a rare type of primary localized cutaneous amyloidosis. Non-invasive techniques can provide important clues for early diagnosis. Objectives: To highlight the characteristic imaging changes of ACD under dermoscopy and reflectance confocal microscopy (RCM), investigate gene mutations in a Chinese Han pedigree of ACD, and analyze the genotype–phenotype correlation. Methods: Dermoscopy and RCM examinations were completed together for the pedigree, and the imaging characteristics were described. The diagnosis of ACD was confirmed by pathological examination. Sequencing was performed followed by bioinformatics and genotype–phenotype correlation. ACD-related articles published on PubMed between January 1970 and March 2021 were reviewed and summarized. Results: In ACD, dermoscopy showed patchy white hypopigmentation and brownish spots, stripes, or hyperpigmented blotches and patches. RCM showed a highly refractive substance with clumpy, dotted, and linear structures inside the papillary dermis. Sequencing identified glycoprotein non-metastatic melanoma protein B (GPNMB) missense mutations [c.393T>G (p.Y131X; NM_001005340.2)] and a frameshift deletion mutation [c.719_720delTG (p.V240fs; NM_001005340.2)]. The ANNOtate VARiation (ANNOVAR) software predicted that c.393T>G is a pathogenic mutation. The literature review found 14 mutations, namely, 5 (35.7%) frameshift mutations, 4 (28.6%) non-sense mutations, 4 (28.6%) missense mutations, and 1 (7.1%) splice site mutation. Blisters and epidermolysis were observed in several cases, but there was no significant association between clinical manifestations and mutations in ACD. Conclusions: This study was the first to combine dermoscopy and RCM to describe ACD. Two GPNMB gene mutations were reported in a Chinese ACD pedigree. The genotype–phenotype correlation was analyzed for the first time; however, there was no significant correlation.